Concentration-Dependent Effects of a Dietary Ketone Ester on Components of Energy Balance in Mice - Deemer, Sarah E.; Davis, Rachel A. H.; Gower, Barbara A.; Koutnik, Andrew P.; Poff, Angela M.; Dickinson, Stephanie L.; Allison, David B.; D'Agostino, Dominic P.; Plaisance, Eric P. (Frontiers in Nutrition, 2019)
Objective: Exogenous ketones may provide therapeutic benefit in treatment of obesity. Administration of the ketone ester (KE) R,S-1,3-butanediol acetoacetate diester (BD-AcAc2) decreases body weight in mice, but effects on energy balance have not been extensively characterized. The purpose of this investigation was to explore concentration-dependent effects of BD-AcAc2 on energy intake and expenditure in mice. Methods: Forty-two male C57BL/6J mice were randomly assigned to one of seven isocaloric diets (n=6 per group): 1) Control (CON, 0% KE by kcals); 2) KE5 (5% KE); 3) KE10 (10% KE); 4) KE15 (15% KE); 5) KE20 (20% KE); 6) KE25 (25% KE); and 7) KE30 (30% KE) for 3 weeks. Energy intake and body weight were measured daily. Fat mass (FM), lean body mass (LBM), and energy expenditure (EE) were measured at completion of the study. Differences among groups were compared to CON using ANOVA and ANCOVA. Results: Mean energy intake was similar between CON and each concentration of KE, except KE30 which was 12% lower than CON (P<0.01). KE25 and KE30 had lower body weight and FM compared to CON, while only KE30 had lower LBM (P<0.03). Adjusted resting and total EE were lower in KE30 compared to CON (P<0.03), but similar for all other groups. Conclusions: A diet comprised of 30% energy from BD-AcAc2 results in lower energy intake, coincident with lower body weight and whole animal adiposity; while KE20 and KE25 have significantly lower body weight and adiposity effects independent of changes in energy intake or expenditure.